PENGEMBANGAN MEDIA PEMBELAJARAN BIG BOOK UNTUK MENINGKATKAN KETERAMPILAN MEMBACA PERMULAAN SISWA KELAS I SEKOLAH DASAR - Hilfa Alipatul Maula; Mulabbiyah; Yuanti Draditaswari , Silka (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was motivated by the importance of beginning reading skills as the foundation of students’ language abilities in early grades. Preliminary findings at SDN 1 Terong Tawah showed that beginning reading instruction was not optimal due to the lack of varied learning media. Teachers mainly relied on textbooks and worksheets, causing low learning motivation, and most students were still at the spelling stage. Therefore, this study aimed to develop a big book learning media to improve students’ beginning reading skills and determine the validity, practicality, and effectiveness of the developed media. This study used a Research and Development (R&D) method with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The subjects were first-grade students of SDN 1 Terong Tawah. Data were collection through interviews, questionnaires, and tests, then analyzed using quantitative and qualitative techniques. The results showed that the developed big book media was highly valid, with an average score of 96%, consisting of media expert validation at 96%, material expert validation at 97%, and language expert validation at 96%. The practicality test showed very practical results with scores of 95% in the small-scale trial and 98% in the large-scale trial. The effectiveness of the media was demonstrated through the results of students’ beginning reading skills tests, with an average score of 89 and classical completeness of 87%, which was categorized as very effective. Thus, the developed big book media is valid, practical, and effective in improving beginning reading skills of first-grade elementary school students.